Women's Retirement Age in Vietnam : Gender Equality and Sustainability of the Social Security Fund - World Bank (World Bank, 2012)
The issue of the retirement age is fundamentally linked to policies on social protection. It is an issue that inevitably causes debate and has proponents, men and women, who argue on both sides. During preparation of the gender equality law in Vietnam, several options were presented for changing the retirement age of women. However, the National Assembly could not make a decision as the debate was rife with mostly emotional arguments. A more constructive dialogue could be pursued if presented with economic and social arguments of each option, or alternative options. During the labor code revision in 2009, this study will hopefully provide a good basis for decision making as well as for further policy dialogue on the issue. The main objective of this study is to provide economic and social arguments on different options for women's retirement age in Vietnam to serve as a basis for further consultation and policy dialogue with the Government.